BUSINESS, SOCIETY, AND GOVERNMENT ESSENTIALS strategy and applied ethics. - Lussier, Robert N.; Sherman, Herbert (ROUTLEDGE, 2022)
Understanding the interrelationship of business, society and government is vital to working at any level in an organization of any size. This text develops strategic management skills using an applied ethics approach, primarily through a case study analysis pedagogy, to develop and implement ethical strategies in today's high-tech global community. The authors crystallize the complex array of issues that business leaders, managers, and employees face in market and nonmarket environments, from balancing stakeholder interests and dealing with government regulations to managing crises and making socially responsible and ethical decisions. Technical concepts come to life through a variety of cases and case questions, thought-provoking personal and professional applications, ethical dilemmas, and practical exercises. Furthermore, an appendix offers approaches to case analysis and includes a case analysis table that serves as a model for students and professors. Thoroughly revised and updated, the third edition includes discussions on the influence of globalization and technology, the impact of COVID-19, and greater focus on developing ethical strategies. With its thorough coverage of relevant issues and skill-building elements to stimulate critical thinking, this text will engage and prepare students to understand and confront real-world business issues by developing and implementing ethical strategies through case analysis of companies and analysis of organizational ethical dilemmas.